A non-invasive prenatal DNA screening test for Down Syndrome - Thilakavathy, Karuppiah; Rosli, Rozita (Penerbit Universiti Sains Malaysia, 2004)
Prenatal diagnosis still depends on invasive methods using cells contained in the amniotic fluid or villus cells (Suzumori, 1999). These procedures carry a small but important rate of miscarriage (Vyas, 1994). The discovery on the presence of foetal cells in maternal circulation was a turning point for the development of a safe, accurate and reliable prenatal diagnosis, which could be offered to as a routine test to any pregnant women regardless their age.